Mapping the binding region of aptamer targeting small molecule: Dabigatran etexilate, an anti-coagulant - Aljohani, Maher M.; Chinnappan, Raja; Alsager, Omar A.; Alzabn, Razan; Alhoshani, Ali; Weber, Karina; Cialla-May, Dana; Popp, Jürgen; Zourob, Mohammed (Talanta, 2020)
Aptamers are single-stranded DNA or RNA, which have attracted considerable scientific interest due to their characteristic of specific and selective binding to target molecules. They are evolved from the in vitro process known as systematic evolution of ligands by exponential enrichment (SELEX). This paper reports a simple experimental approach to elucidate the binding region of small targets binding aptamers. A previously isolated 60-mer aptamer for the anti-coagulant dabigatran etexilate (DBG) was used for this investigation. Complimentary sequences labelled with a fluorophore and a quencher were used for testing the binding region by change in the fluorescence signal. The full-length aptamer was truncated to multiple shorter copies including a 38 nucleotides sequence that showed 47 fold high affinity compared to the original aptamer. Circular dichroism spectroscopy (CD) measurements indicate that the 38-mer is remarkably more sensitive than the parent aptamer. The truncated 38-mer sequence was used to construct a turn-on fluorescence sensor with the detection limit of 1 nM. The performance of the sensor was examined in blood serum samples and showed excellent recovery percentages exceeding 98%. The reported screening protocol could be applied to the growing small targets aptasensors that require efficient binding aptamer sequences coupled with optimum signal transduction methods.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Aptasensors; Circular dichroism; Dabigatran etexilate; Fluorescence; Target binding region; Truncation